2007
DOI: 10.1104/pp.107.107730
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Interactions between DNA Demethylation and Methylation in Arabidopsis

Abstract: DNA demethylation in Arabidopsis (Arabidopsis thaliana) is mediated by DNA glycosylases of the DEMETER family. Three DEMETER-LIKE (DML) proteins, REPRESSOR OF SILENCING1 (ROS1), DML2, and DML3, function to protect genes from potentially deleterious methylation. In Arabidopsis, much of the DNA methylation is directed by RNA interference (RNAi) pathways and used to defend the genome from transposable elements and their remnants, repetitive sequences. Here, we investigated the relationship between DML demethylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 35 publications
3
82
0
Order By: Relevance
“…We tested and found that the dtf1-1 mutation did not affect Pol V-dependent transcripts, while loss of the largest subunit of Pol V, NRPE1, blocked accumulation of the Pol V-dependent transcripts, including AtSN1 B and IGN5 B ( Figure 3A). Previous studies showed that mutations in canonical RdDM components suppress ROS1 expression [21,48,49]. We found that the dtf1-1 mutation also suppressed the expression of ROS1 ( Figure 3A).…”
Section: Dtf1 Is Required For the Silencing Of Some Endogenous Rddm Tsupporting
confidence: 63%
“…We tested and found that the dtf1-1 mutation did not affect Pol V-dependent transcripts, while loss of the largest subunit of Pol V, NRPE1, blocked accumulation of the Pol V-dependent transcripts, including AtSN1 B and IGN5 B ( Figure 3A). Previous studies showed that mutations in canonical RdDM components suppress ROS1 expression [21,48,49]. We found that the dtf1-1 mutation also suppressed the expression of ROS1 ( Figure 3A).…”
Section: Dtf1 Is Required For the Silencing Of Some Endogenous Rddm Tsupporting
confidence: 63%
“…This is surprising because heterochromatic siRNAs are substantially diminished in rdr2, which one might have suspected would lead to stochastic activation of transposons and the generation of epialleles, such as reported for the ddm1 in Arabidopsis that dramatically reduces DNA methylation within repeats (27). However, it has been suggested that the rdr2 mutation causes a decrease in production of the demethylase ROS1, leading to hypermethylation at CG sites and additional protection against the activation of transposons (28). A more complete understanding of transposon reactivation in rdr2 and mop1 mutants will await larger-scale studies of DNA methylation in these mutants.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, the local DNA hypermethylation observed in ros1dml2dml3 is frequently associated with overaccumulation of matching siRNAs (Lister et al, 2008). Moreover, many second-site suppressors of ros1-induced hypermethylation and silencing are components of the RdDM machinery (Zheng et al, 2007;Penterman et al, 2007a;He et al, 2009a, b). These observations imply that at some loci, DNA methylation patterns result from the opposing action of RdDM and DNA demethylation.…”
Section: Interplay Between Dna Methylation and Demethylation Mechanismsmentioning
confidence: 99%